Psychosemantics : the problem of meaning in the philosophy of mind - Fodor, Jerry A. (Explorations in cognitive science, 1987)
Psychosemantics explores the relation between commonsense psychological theories and problems that are central to semantics and the philosophy of language. Building on and extending Fodor's earlier work it puts folk psychology on firm theoretical ground and rebuts externalist, holist, and naturalist threats to its position. --From publisher's description.